The tectonic shift in Fernando Távora’s work in the Post-CIAM years - FERNANDES, Eduardo (CEAA/ESAP-CESAP, 2019)
Between 1955 and 1960 the Portuguese architect Fernando Távora (1923-2005) designed an important group of buildings: the municipal market of Vila da Feira, the house in Ofír, the tennis pavilion of Quinta da Conceição in Leça da Palmeira and the primary school of Cedro in Gaia. These buildings are landmarks in the history of Portuguese architecture; in their design, Távora employed traditional materials (stone, timber, tile) and reused vernacular construction techniques (bearing walls, wooden beams and pitched roofs) within a modern approach. This attitude is directly related to the results of the Surveys on Portuguese Vernacular Architecture, promoted by the Union of the Portuguese Architects between 1955 and 1960 and conducted by some of the most renowned Portuguese architects; Fernando Távora was responsible for the work in ‘Zone 1’ and learned how to recognize the presence of a certain kind of ‘modernity’ in the Vernacular Architecture of the north of the country. However, after 1960 his language changed and the direct influence of the vernacular began to be less obvious. In order to understand the evolution of his work at this time, it is important to remember that Távora was present at the main international architectural meetings, where he had the opportunity to contact the key names of the worldwide architectural community: he integrated the Portuguese representations present in the last CIAM Congresses and also participated in the Royaumont meeting of the Team Ten. Besides, in 1960 Távora made a three-month journey to the United States and participated in the World Design Conference in Japan. These international contacts and experiences were important to the rethinking of concepts that led to the different languages we can find in the buildings he designed after 1960.
This work has the financial support of the Project Lab2PT - Landscapes, Heritage and Territory laboratory - AUR/04509 and FCT through national funds and when applicable of the FEDER co-financing, in the aim of the new partnership agreement PT2020 and COMPETE2020 - POCI 01 0145 FEDER 007528.
Keywords: Távora; CIAM; Team Ten; Vernacular; Modern